Microduplication of Xp22.31 and MECP2 Pathogenic Variant in a Girl with Rett Syndrome: A Case Report - Estephania Candelo; Diana Ramirez-Montaño; Harry Pachajoa (Iranian Journal of Medical Sciences, 2019)
Rett syndrome (RS) is a neurodevelopmental infantile disease characterized by an early normal psychomotor development followed by a regression in the acquisition of normal developmental stages. In the majority of cases, it leads to a sporadic mutation in the MECP2 gene, which is located on the X chromosome. However, this syndrome has also been associated with microdeletions, gene translocations, and other gene mutations.A 12-year-old female Colombian patient was presented with refractory epilepsy and regression in skill acquisition (especially language with motor and verbal stereotypies, hyperactivity, and autistic spectrum disorder criteria). The patient was born to non-consanguineous parents and had an early normal development until the age of 36 months. Comparative genomic hybridization array-CGH (750K) was performed and Xp22.31 duplication was detected (6866889-8115153) with a size of 1.248 Mb associated with developmental delay, epilepsy, and autistic traits. Given the clinical criteria of RS, MECP2 sequencing was performed which showed a de novo pathogenic variant c.338C>G (p.Pro113Arg).The features of RS include intellectual disability, developmental delay, and autism. These features are associated with copy number variations (CNVs) on the X chromosome (Xp22.31 microduplication). Here we present the first reported case of simultaneous CNV and MECP2 pathogenic mutation in a patient with RS. We propose that both DNA alterations might have a synergistic effect and could lead to variable expressivity of the phenotype.